(untitled) (Research, Society and Development, 2020)
There are several instruments, such as manuals and booklets that provide guidelines for the management of construction waste in Brazil, that were development based on CONAMA Resolucion n° 307/2002. However, most of the files publicly available were developed previously to the current Brazilian legislation (Law n. 12.305/2010). This paper aims to analyze manuals and booklets electronically available on the planning and implementation of construction waste management in Brazilian construction sites. The methodology used was based on the evaluation of the design of the work taking into account 5 categories (objective, organization, writing style, appearance and motivation) subdivided by 17 items (classified using a Likert scale) and both theoretical and practical content evaluation to identify the presence of items according to the guidelines of Law No. 12.305/2010, Resolution No. 307/2002 of CONAMA, technical standards, books and scientific articles. The results showed that, regarding the design, in general, all the analyzed materials are well presented, and were classified as good or very good. However, regarding the content, none presented all the items requested by the current legislation. As they are available to the public and can be used as a basis for planning and implementing the GRCC, materials prior to the law require updating and, later, a revision to insert the contents not mentioned. In this way, the results of this study may help authors and publishers in this process, with each item listed and not included in the respective materials being pointed out here.